Analyzing Trends in Key Financial Indicators: A Case Study on ORION Pharma Limited - Ahamed, Mohammad Jafaur (Asian Business Review, 2024)
This descriptive research study aims to examine the performance trends of ORION Pharma Limited within the context of its operations in Bangladesh. The study is based on secondary data extracted from annual reports spanning from FY 2018-19 to 2022-23 of the chosen company. It employs trend percentage analysis on key financial metrics derived from these reports. Firstly, the analysis focuses on fluctuations in key financial indicators of the statement of profit or loss, such as net sales revenue, gross profit, operating profit, pre-tax profit, and post-tax profit. Despite facing challenges, the company has shown resilience and adaptability, showcasing noticeable recoveries and improvements during different periods. These changes reflect ORION Pharma’s responsiveness to market conditions and efforts to manage expenses efficiently. The analysis suggests opportunities for strategic expansions and profit enhancements despite occasional setbacks. Secondly, examining the trend percentage of key metrics of the statement of financial position for ORION Pharma, the study shows consistent growth in total assets, driven by expansions in both current and non-current assets. Though liabilities increased notably, total equity showed positive growth, indicating effective management and sustained profitability. In summary, ORION Pharma demonstrates strong financial performance and strategic planning, positioning it for continued growth and profitability.